Pemberlakuan Whistle Blowing System Dalam Penegakan Hukum Pemilu Dan Penanganan Pelanggaran Kode Etik Penyelenggara Pemilu - Rene Zakharia Pongsiluang; Tri Susilowati (Universitas Sains dan Teknologi Komputer, 2023)
Incidents of violations of the code of ethics are very common, but it is possible that there are also many cases where no complaints are filed due to the reluctance of election participants to make complaints because the process is litigious or they don't want to be bothered with legal matters. Or maybe because election organizers have developed a spirit of solidarity with the election organizer corps. This article was written with the aim of analyzing the implementation of the whistle blowing system in enforcing election law and handling violations of the code of ethics for election organizers. This research is a type of normative juridical research. The realization of the idea of ​​a Whistle Blowing System Mechanism in Handling Violations of the Code of Ethics for Election Organizers can be carried out if the legal basis for enforcing the code of ethics that is currently in effect is the law on election organizers and the Regulation of the Honorary Council for Election Organizers of the Republic of Indonesia number 1 of 2013 concerning procedural guidelines for organizers' code of ethics. the general election was changed by including the three aspects above. Therefore, the DPR and the President should revise the election organizer law and the DKPP should revise the Regulation of the Honorary Council for General Election Organizers of the Republic of Indonesia number 1 of 2013 concerning procedural guidelines for the code of ethics for general election organizers.